2006
DOI: 10.1016/j.amjcard.2005.11.038
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness and Safety of Percutaneous Coronary Interventions for Cardiac Transplant Vasculopathy

Abstract: Late morbidity and death as a result of progressive coronary vascular obliteration remains a major unsolved problem after orthotopic heart transplantation. Various percutaneous catheter intervention (PCI) methods have been used to treat transplant coronary artery disease (CAD), but few reports have assessed the longitudinal results of these procedures. Of 1,440 cardiac transplant patients at University of California, Los Angeles, Medical Center, treated between 1984 and 2004, 65 patients who had undergone orth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
2
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 22 publications
3
48
2
2
Order By: Relevance
“…The risk of restenosis is perceived to be usually higher in patients after heart transplantation than in the native heart [13]. Aquel et al, Tanaka et al, and Lekston et al demonstrated that DES implantation results in lower risk of restenosis as compared to BMS [14][15][16]. We were not able to confirm that finding, probably due to the relatively small number of patients with only 2 incidents of restenosis.…”
Section: Discussioncontrasting
confidence: 54%
“…The risk of restenosis is perceived to be usually higher in patients after heart transplantation than in the native heart [13]. Aquel et al, Tanaka et al, and Lekston et al demonstrated that DES implantation results in lower risk of restenosis as compared to BMS [14][15][16]. We were not able to confirm that finding, probably due to the relatively small number of patients with only 2 incidents of restenosis.…”
Section: Discussioncontrasting
confidence: 54%
“…One of the main concerns of PCI in OHT patients is re-stenosis, as the allografted coronary vessel is in a proinflammatory state, which influences vessel remodeling (13)(14)(15)(16). Multivariate analysis revealed that in allograft vasculopathy, the use of stents decreased the risk of restenosis (odds ratio 0.34, p<0.05) compared with cutting balloon or other PCI methods (10,17). PCI allows a high level of primary success with a low procedural-complication rate (9).…”
Section: Discussionmentioning
confidence: 94%
“…PCI allows a high level of primary success with a low procedural-complication rate (9). In addition, the restenosis rate with drug-eluting stents is reported to be 15-19%, which is lower than bare metal stent (31%) (10,17).…”
Section: Discussionmentioning
confidence: 99%
“…A high restenosis rate may be reflective of the underlying inflammatory nature of TCAD. Two studies reported trends toward lower restenosis rates with DES compared with bare-metal stents in OHT patients [12,45]. In one report, two OHT patients who underwent ULMCA PCI with bare-metal stents for TCAD developed restenosis and underwent coronary artery bypass surgery [34] (Table II).…”
Section: Discussionmentioning
confidence: 98%